PROMOTING THE INTERNET TO STUDENTS OF SMK TRISULA DOLOK SANGGUL - Edy (Jurnal Prinsip Pengabdian Masyarakat, 2025)
Rapidly development technology Internet Which No accompanied with education in its use causes internet addiction and tends to using the internet for useless things even negative. Because That writer do PKM with title " INTRODUCING THE INTERNET TO STUDENTS OF SMK TRISULA DOLOK SANGGUL ". Community service to SMK Trisula Dolok Sanggul (PKM) aims to Educating students in the use of the internet, especially students of Trisula Dolok Sanggul Vocational School . The conclusions that can be drawn from the Community Service activities at Trisula Dolok Sanggul Vocational School are: 1. The students who attended the counseling responded warmly and expressed deep appreciation. in relation to the activity, 2. When delivering the material, participants understand how to sort the information provided. internet bars, maintaining internet security, one of which is from phishing crimes and tips for staying productive in working or studying, 3. Participants can answer the questions given well and respond positively is a sign that the extension material has been delivered, 4. Male and female students participating in PKM receive knowledge knowledge new and get certificate participation that is given by organizer activity.